Keeping Track of Greenhouse Gas Emission Reduction Progress and Targets in 167 Cities Worldwide - Wei, Ting; Wu, Junliang; Chen, Shaoqing (Frontiers in Sustainable Cities, 2021)
Actions in cities shape the outcome of greenhouse gas (GHG) emission mitigation and our climate change response. Accurate and consistent carbon inventories are essential for identifying the main sources of emissions and global comparison of carbon reduction progress and would help inform targeted policies for low-carbon transition. To identify the effectiveness of historical carbon reduction policies, our study conducted energy-related GHG emission inventories for 167 globally distributed cities with information from different sectors, and assessed the city-scale near-term, mid-term, and long-term goals carbon mitigation targets from 2020 to 2050. On this basis, we propose mitigation strategies to achieve local and global climate targets. We found that, although Asian cities are the biggest carbon emitters in totals, the per capita GHG emissions of cities in developed countries are still generally higher than that in developing countries. In terms of sectors, the GHG emissions from the stationary energy uses (such as residential, commercial and industrial buildings) and transportation sector contributed the most. However, cities in more developed nations have been inclined to set absolute carbon reduction targets before 2050, while intensity reduction target has been largely set for cities at the stage of rapid economic growth and accelerated industrialization. More ambitious and easily-tracked climate targets should be proposed by cities and more effective measures of reducing GHG emissions are required to stay consistent with the global ambition of climate change mitigation.